Dexmedetomidine-Induced Contraction Involves CPI-17 Phosphorylation in Isolated Rat Aortas - Seong-Ho Ok (International Journal of Molecular Sciences, 2016)
Dexmedetomidine, a highly selective α-2 adrenoceptor agonist, produces vasoconstriction, which leads to transiently increased blood pressure. The goal of this study was to investigate specific protein kinases and the associated cellular signal pathways responsible for the increased calcium sensitization induced by dexmedetomidine in isolated rat aortas, with a particular focus on phosphorylation-dependent inhibitory protein of myosin phosphatase (CPI-17). The effect of Y-27632 and chelerythrine on the dexmedetomidine-induced intracellular calcium concentration ([Ca2+]i) and tension were assessed using fura-2-loaded aortic strips. The effects of rauwolscine, Y-27632, chelerythrine, and ML-7 hydrochloride on the dexmedetomidine-induced phosphorylation of CPI-17 or of the 20-kDa regulatory light chain of myosin (MLC20) were investigated in rat aortic vascular smooth muscle cells. The effects of rauwolscine, Y-27632, and chelerythrine on the membrane translocation of Rho-kinase and protein kinase C (PKC) phosphorylation induced by dexmedetomidine were assessed. Y-27632 and chelerythrine each reduced the slopes of the [Ca2+]i-tension curves of dexmedetomidine-induced contraction, and Y-27632 more strongly reduced these slopes than did chelerythrine. Rauwolscine, Y-27632, chelerythrine, and ML-7 hydrochloride attenuated the dexmedetomidine-induced phosphorylation of CPI-17 and MLC20. Taken together, these results suggest that dexmedetomidine-induced contraction involves calcium sensitization, which appears to be mediated by CPI-17 phosphorylation via Rho-kinase or PKC.